A Clinical Study of Hypothyroidism Associated With Type – 2 Diabetes Mellitus (Academia Journal of Medicine, 2020)
Background: Thyroid disorders are common in the general population and the incidence of type 2 diabetes mellitus is also rapidly increasing day by day. The objective is to determine the age and sex prevalence, pattern of presentation and management of patients suffering from hypothyroidism associated with type-2 diabetes mellitus. Subjects and Methods: Design: The study was an observational study of 20 types 2 diabetics attending the Department of Medicine (outpatient/inpatient). Duration: 1 year i.e. from December 2004 – December 2005. Setting: Out-patient department. Participants:20 patients with both Diabetes Mellitus type 2 and Hypothyroidism. Patients with known diabetes attending OPD were considered. Data were collected using a standardized case report form. Results: The majority of the patients had got diagnosed with hypothyroidism and diabetes within a span of 0 to 5 years, followed by 6 to 9 years span with 4 patients and 3 patients within the span of 10 to 14 years and 2 patients in the span of 15 to 19 years. Only 1 patient was diagnosed with both in a span of 20- to 24 years and one patient in 25 to 29 years. Conclusion: Annual Screening is mandatory in all hypothyroid patients for the early detection and treatment of diabetes mellitus, thereby to prevent and/or postpone the complications of diabetes, and all diabetes mellitus patients to undergo thyroid function screening (TFT) yearly for the early detection of thyroid dysfunction and thereby reducing the morbidity and mortality.
Keywords: Hypothyroidism; Diabetes Mellitus